Proof of Pseudonym: Blockchain-Based Privacy Preserving Protocol for Intelligent Transport System - S. Johar; N. Ahmad; A. Durrani; G. Ali (IEEE Access, 2021)
Intelligent Transportation System is the future for safe and secure transportation. Vehicles in the ITS share basic safety information which can prompt the disclosure of the real identity of the vehicles. Thus, adversaries can misuse these safety messages. Pseudonyms are alias granted to vehicles by trusted authorities to conceal their original identities. To avoid linkability, various pseudonym generation and distribution protocols have been proposed. Such protocols pose overheads in the system as they are performed by Central Authorities. Therefore, re- utilizing the existing pseudonyms through shuffling is the most optimal mechanism for ITS. The Blockchain is a digital ledger and tamper-resistant record of transactions. It eliminates the need for central authority as well as provides anonymity of transactions resulting in more secure and privacy-protected solutions. To handle distribution optimization issues in the pseudonym shuffling process without a central authority, the blockchain is used with its distributed consensus. The shuffling results are logged in blocks as transactions. Pseudonym shuffle randomness is achieved via blockchain and it provides robustness in the structure. When one system fails, the rest would continue to work. The method also provides a fully traceable record in case of certification revocation. The existing blockchain-based pseudonym shuffling mechanism uses traditional consensus algorithms to support the cryptography operation. This leads to overhead in terms of execution time and memory usage. This research proposes Proof of Pseudonym consensus protocol for the shuffling scheme to improve the efficiency of consensus as compared to Proof of Work, Proof of Kernel Work and, Proof of Elapsed Time in terms of time and memory. The execution time of Proof of Pseudonym is shorter than other algorithms. The security and privacy analysis revealed that our scheme achieves identity privacy, unlinkability, and non-repudiation properties. Threat analysis evaluates the proposed protocol in terms of both internal and external attacks.